Strategi Pengembangan Kampung 99 Pepohonan Sebagai Daya Tarik Wisata Edukasi di Kota Depok - Jody Darmawan; Hindun Nurhidayati (Journal of Tourism Destination and Attraction, 2019)
Educational tour or educational tour is a program that combines elements of tourism activities with the content of informal education in it. This program is packaged in such a way to be an annual tourism activity or extracurricular activities that have quality and weight for participants who follow this educational tour, the material to be used in this tour has been adjusted to the weight of participants and what information will be provided. village 99 Trees is one of the objects of educational-based tourism destination that provides tourism activities in the area of forest conservation and nature. The objective of the study was to identify the educational potential of Village 99 area and to develop education development strategy in village 99 area. The method used in this research is qualitative method, data collection with observation, questionnaire and documentation. Data analysis in this study using SWOT analysis.The result of the research is SO's strategy which involves involving local communities in the development of educational tourism. Establishing cooperation with gold dome managers related to tourist management, Maintaining beautiful environmental conditions to keep cool, making group tour packages using fish objects.